Sustained modulation of intestinal bacteria by exclusive enteral nutrition used to treat children with Crohn’s disease - LEACH, S. T.; MITCHELL, H. M.; ENG, W. R.; ZHANG, L.; DAY, A. S. (Alimentary pharmacology & therapeutics, 2008)
Summary Background  The use of exclusive enteral nutrition to treat paediatric Crohn’s disease (CD) is widely accepted, although the precise mechanism(s) of action remains speculative. Aim  To investigate the changes to key intestinal bacterial groups of Eubacteria, Bacteroides, Clostridium coccoides, Clostridium leptum and Bifidobacteria, during and after exclusive enteral nutrition treatment for CD in paediatric patients and correlate these changes to disease activity and intestinal inflammation. Methods  Stool was collected from six children at diagnosis of CD, during exclusive enteral nutrition and 4 months post‐therapy, and from seven healthy control children. The diversity of bacteria was assessed by polymerase chain reaction‐denaturing gradient gel electrophoresis with changes to bacterial diversity measured by Bray–Curtis similarity, intestinal inflammation assessed by faecal S100A12 and the disease activity assessed by PCDAI. Results  A significantly greater change in intestinal bacterial composition was seen with exclusive enteral nutrition treatment compared with controls. Further, the intestinal bacteria remained altered 4 months following exclusive enteral nutrition completion. Changes in the composition of Bacteroides were associated with reduced disease activity and inflammation. Conclusions  Exclusive enteral nutrition reduces bacterial diversity and initiates a sustained modulation of all predominant intestinal bacterial groups. Exclusive enteral nutrition may reduce inflammation through modulating intestinal Bacteroides species. The implications of these results for exclusive enteral nutrition therapy and CD pathogenesis should now be the subject of further investigation.